Treinamento em estratégias focadas na solução de problemas: prevenção ao stress do professor - Biazzi, Sideli (2017)
This study aimed to verify the effectiveness of a stress reduction training, based on the promotion of strategies focused on problem solving. To achieve such objective, the research was divided into two stages, the first as a diagnostic selection procedure (with the participation of 278 teachers). From this total, 148 (53.23%) presented stress, most of them in the resistance phase (42.1%) with prevalence of psychological stress (68.92%). Women, a predominant portion of the studied population (84.9%), presented a higher level of stress when compared to men (p <0.0001). In the second phase, among the 148 teachers who presented stress, a draw was held with the purpose of forming three groups (30 teachers each group): Experimental Group (EG), Control Group (CG) and Placebo Group (GP), with evaluations pre- and post-intervention. The EG followed a stress reduction program by means of a problem-focused training; the PG received a pedagogical training offered by the Institution's Education Department (the pedagogical training and the stress reduction program were carried out for five days at the Training Center of Cotia, SP, as a 36-hour immersion course); the CG did not receive any intervention, maintaining their regular work activities. Participants were tested at three different moments: T0 (before intervention), T1 (30 days after EG treatment), and T2 (90 days after EG treatment), through the Lipp Adult Stress Symptom Inventory (ISSL), the Cope Breve Scale (for EG only), and the Visual Analogue Scale - VAS (for EG only, used at the beginning and at the end of each intervention day). The intervention results demonstrated that the EG teachers presented a statistically significant reduction in stress symptoms. In addition, it was found that the training was also effective in promoting the use of strategies focused on problem solving and in significantly reducing the use of strategies focused on emotion. Such changes remained after 90 days of training. The PG also achieved statistically significant results as to the presence or absence of stress – the T1 evaluation showed a reduction in stress level; however, after 90 days the EG teachers’ stress level was significantly lower than the PG’s. For the CG, no significant difference was detected when evaluating the proportion of individuals in the respective phases of stress, either as to the stress symptomatology or the presence or absence of stress over the 30 and 90 days. It can be noticed that the EG improvement was superior to those attained by PG and CG. The positive results achieved by EG indicate that, although teachers coexist with high levels of stress throughout their lives, if well oriented they can find effective ways of managing their stressors